O processo de institucionalização sociocognitiva do domínio de Organização do Conhecimento a partir dos trabalhos científicos dos congressos da ISKO - Arboit, Aline Elis [UNESP] (2014)
To describe and interpret part of the ongoing process of sociocognitive institutionalization of domain of Knowledge Organization (KO) is the central aim of this study. For that, we proceeded to diachronic analysis of language used, expressed and registered by scientific community at conferences of the International Society for Knowledge Organization (ISKO), understanding this entity as representative of the domain due to the central role it acquires. The scientific production of sponsored events by ISKO are considered valuable source to detect dominant ideological positions taken periodically via discourse analysis set out in documents. Thus, issues related to language, memory and knowledge as a result of the interaction between the subject and its environment have been addressed. Was sought theoretical support on Bakhtin Circle (CB), especially with regard to social and ideological character of the linguistic sign and the concept dialogism between signs, pillar that supports the author's thesis about the social character of language. Conceptions on the relationship between individual memory and the collective memory and the dialogism treated as a memory medium and thus a means of access of knowledge. Were selected from the theoretical areas of IC and KO concepts that address the implications of these for interactive production, organization and use of information and knowledge processes activities. Regarding the process of institutionalization, subsidies were sought up primarily in the design of Whitley (1974) on the concept of scientific institutionalization and social cognitive character of science and the mutual relationship of both. Information constituents of the domain of theoretical frameworks were brought from KO, elaborating a diachronic analysis of the process of theorizing based on the use of the term Knowledge Organization, regarding the first theoretical formulations on bibliographic classification discipline. Then, the...